2021
DOI: 10.32598/jpcp.9.3.768.1
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Social Safeness and Self-compassion in Mental Health Problems: A Model Based on Gilbert Theory of Emotion Regulation Systems

Abstract: Objective: This study aimed to investigate the role of social safeness and self-compassion, as two essential components of Gilbert’s theory, in mental health. In this regard and based on theoretical foundations, the mediation model of the relationship between social safeness and mental health problems was examined through self-compassion as a mediator. Methods: A total of 344 students from the University of Bojnord, Bojnord City, Iran, in the 2019-2020 academic year were recruited using the cluster sampling me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…In previous studies, social safeness has been found to be distinguishable from both PA and NA, supporting discriminant validity [7], and difficulties in the development of social safeness have been suggested to be a transdiagnostic vulnerability factor [6,12,13]. Indeed, our results showed significantly lower scores for social safeness in our clinical samples compared with the NC sample.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In previous studies, social safeness has been found to be distinguishable from both PA and NA, supporting discriminant validity [7], and difficulties in the development of social safeness have been suggested to be a transdiagnostic vulnerability factor [6,12,13]. Indeed, our results showed significantly lower scores for social safeness in our clinical samples compared with the NC sample.…”
Section: Discussionsupporting
confidence: 83%
“…Further, difficulties in achieving social safeness and pleasure has been suggested as a transdiagnostic vulnerability factor for different psychological problems [2,12]. There is also evidence that therapeutic interventions targeting social safeness and pleasure can be beneficial [13].…”
Section: Introductionmentioning
confidence: 99%
“…A strong sense of social safeness protects against depression, anxiety and stress by increasing self-compassion (Alavi, 2021). As a result, the following hypothesis can be formed:…”
Section: Social Safeness and Life Satisfactionmentioning
confidence: 99%